A systems immunology approach to investigate cytokine responses to viruses and bacteria and their association with disease - Lin, Lijing; Curtin, John A.; Regis, Eteri; Hirsman, Aurica; Howard, Rebecca; Tutino, Mauro; Edwards, Michael R.; Prosperi, Mattia; Simpson, Angela; Rattray, Magnus; Custovic, Adnan; Johnston, Sebastian L. (Scientific Reports, 2022)
Patterns of human immune responses to viruses and bacteria and how this impacts risk of infections or onset/exacerbation of chronic respiratory diseases are poorly understood. In a population-based birth cohort, we measured peripheral blood mononuclear cell responses (28 cytokines) to respiratory viruses and bacteria, Toll-like receptor ligands and phytohemagglutinin, in 307 children. Cytokine responses were highly variable with > 1000-fold differences between children. Machine learning revealed clear distinction between virus-associated and bacteria-associated stimuli. Cytokines clustered into three functional groups (anti-viral, pro-inflammatory and T-cell derived). To investigate mechanisms potentially explaining such variable responses, we investigated cytokine Quantitative Trait Loci (cQTLs) of IL-6 responses to bacteria and identified nine (eight novel) loci. Our integrative approach describing stimuli, cytokines and children as variables revealed robust immunologically and microbiologically plausible clustering, providing a framework for a greater understanding of host-responses to infection, including novel genetic associations with respiratory disease.
CRIS-Team Scopus Importer:2022-08-19